Pandangan Al-Qur’an Terhadap Persepsi Istilah Hari Sial Masyarakat Desa. Mojorejo Kec. Pungging Kab. Mojokerto - Mokhammad Saifuddin Azzuhri; Amir Mahmud; Wiwin Ainis Rohtih; Nyoko Adi Kuswoyo (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2024)
This study explores the beliefs of the people of Mojorejo Village, Pungging District, Mojokerto Regency towards the concept of "unlucky days" from an Islamic perspective. Although this belief has persisted since the time of ignorance, Islam emphasizes that there is no day that inherently brings bad luck or good fortune, because everything that happens is part of the destiny of Allah SWT. By using the approach of analyzing the text of the Qur'an and interpretation, this study aims to provide a more rational and spiritual understanding, and encourage people to abandon beliefs that are not in accordance with Islamic teachings. This study analyzes the beliefs of the people of Mojorejo Village, Pungging District, Mojokerto Regency towards the concept of "unlucky days," especially in the month of Suro, and evaluates this belief from an Islamic perspective. Although this belief is strong and has been passed down from generation to generation, Islam rejects the concept of "unlucky days" and teaches that everything that happens is part of the destiny of Allah SWT. This study uses a sociological and phenomenological approach to understand how the perception of unlucky days is formed in a social and cultural context. The results show that this belief is contrary to Islamic teachings and needs to be replaced with a more rational and spiritual understanding. Abstrak Penelitian ini mengeksplorasi kepercayaan masyarakat Desa Mojorejo, Kecamatan Pungging, Kabupaten Mojokerto terhadap konsep "hari sial" dalam perspektif Islam. Meskipun kepercayaan ini masih bertahan sejak zaman jahiliyah, Islam menegaskan bahwa tidak ada hari yang secara inheren membawa kesialan atau keberuntungan, karena segala sesuatu yang terjadi adalah bagian dari takdir Allah SWT. Dengan menggunakan pendekatan analisis teks Al-Qur'an dan tafsir, penelitian ini bertujuan untuk memberikan pemahaman yang lebih rasional dan spiritual, serta mendorong masyarakat meninggalkan kepercayaan yang tidak sesuai dengan ajaran Islam. Penelitian ini menganalisis kepercayaan masyarakat Desa Mojorejo, Kecamatan Pungging, Kabupaten Mojokerto terhadap konsep "hari sial," terutama di bulan Suro, serta mengevaluasi keyakinan ini dari perspektif Islam. Meskipun kepercayaan ini kuat dan diwariskan turun-temurun, Islam menolak konsep "hari sial" dan mengajarkan bahwa segala sesuatu yang terjadi adalah bagian dari takdir Allah SWT. Penelitian ini menggunakan pendekatan sosiologis dan fenomenologis untuk memahami bagaimana persepsi hari sial terbentuk dalam konteks sosial dan kultural. Hasilnya menunjukkan bahwa keyakinan ini bertentangan dengan ajaran Islam dan perlu digantikan dengan pemahaman yang lebih rasional dan spiritual.